1992
DOI: 10.1177/096394709200100202
|View full text |Cite
|
Sign up to set email alerts
|

The parliamentary Hansard ‘verbatim’ report: the written construction of spoken discourse

Abstract: In this article I want to contribute to the critical linguistic analysis of discourse representation practices in an institutional context. I focus on the minutes of the British parliamentary proceedings. My method is that of a detailed comparison of the printed text of the report against transcripts of the spoken debates. I begin by proposing two central premises for a theory of discourse representation. Applying these to the Hansard data, two fundamental tendencies are noted which reflect the impact of macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(44 citation statements)
references
References 4 publications
0
43
0
1
Order By: Relevance
“…Berk-Seligson (1990), for example, argues that court interpreters, though thought to be rendering the Spanish spoken by witnesses into English so that the court may understand it, are in fact actually changing what litigants say in the process. Several other researchers (see Walker 1990;Slembrouck 1992;Coulthard 1996) show how written representations, often thought of as the ocial record are signi®cantly altered versions of the oral speech they are meant to represent. The data shown in the foregoing suggest that divergent norms and ways of narrating taboo subjects pose yet another threat to the potential of institutional memory to represent events.…”
Section: Discussionmentioning
confidence: 98%
“…Berk-Seligson (1990), for example, argues that court interpreters, though thought to be rendering the Spanish spoken by witnesses into English so that the court may understand it, are in fact actually changing what litigants say in the process. Several other researchers (see Walker 1990;Slembrouck 1992;Coulthard 1996) show how written representations, often thought of as the ocial record are signi®cantly altered versions of the oral speech they are meant to represent. The data shown in the foregoing suggest that divergent norms and ways of narrating taboo subjects pose yet another threat to the potential of institutional memory to represent events.…”
Section: Discussionmentioning
confidence: 98%
“…However, we decided that including such a disproportionate amount of linguistic details would have distracted our audience from the central points of our analyses. We decided that excessive attention to the thoroughness of our transcripts could have prevented us from addressing what we felt was at stake at those transcripts (Slembrouck, 1992). Furthermore, such a technical and detailed transcription could have potentially limited accessibility to our transcripts as well as their utility to our audience that consists primarily of science educators, not linguist scholars.…”
Section: Evaluation and Transcriptionmentioning
confidence: 98%
“…The transcripts are thus "thrice removed from the original" (Mollin, 2007, p. 189). Slembrouck (1992) suggested that the process of producing the Hansard report in this way acts to embody "institutional assumptions about what is more or less important in parliamentary discourse representation" (1992, p. 117). The "writtenness" of the record acts to filter out the "spokenness" of language and targets "explicitness" and "well-formedness" of expression (1992, pp.…”
Section: Hansardmentioning
confidence: 99%